Effects of continuous positive airway pressure therapy withdrawal in patients with obstructive sleep apnea A randomized controlled trial - Kohler, M; Stoewhas, A; Ayers, L; Senn, O; Bloch, K; Russi, E; Stradling, JR (2011)
Rationale: To establish a new approach to investigate the physiological effects of obstructive sleep apnea (OSA), and to evaluate novel treatments, during a period of continuous positive airway pressure (CPAP) withdrawal. Objectives: To determine the effects of CPAP withdrawal. Methods: Forty-one patients with OSA and receiving CPAP were randomized to either CPAP withdrawal (subtherapeutic CPAP), or continued CPAP, for 2 weeks. Polysomnography, sleepiness, psychomotorperformance, endothelial function, blood pressure (BP), heart rate (HR), urinary catecholamines, blood markers of systemic inflammation, and metabolism were assessed. Measurements and Main Results: CPAP withdrawal led to arecurrence of OSA within a few days and a return of subjective sleepiness, but was not associated with significant deterioration of psychomotor performance within 2 weeks. Endothelial function, assessed by flow-mediated dilatation, decreased significantly in the CPAP withdrawal group compared with therapeutic CPAP (mean difference in change, -3.2%; 95% confidence interval [CI], -4.5, -1.9%; P < 0.001). Compared with continuing CPAP, 2 weeks of CPAP withdrawal was associated with a significant increase in morning systolic BP (mean difference in change, 18.5 mm Hg; 95% CI, +1.7, +15.3 mm Hg; P=0.016), morning diastolic BP (mean difference in change, +6.9 mm Hg; 95% CI, +1.9, +11.9 mm Hg; P =0.008), and morning HR (mean difference in change, +6.3 bpm, 95% CI, +0.4, +12.2 bpm; P = 0.035). CPAP withdrawal was associated with an increase in urinary catecholamines but did not lead to an increase in markers of systemic inflammation, insulin resistance, or blood lipids. Conclusions: CPAP withdrawal usually leads to a rapid recurrence of OSA, a return of subjective sleepiness, andis associated with impaired endothelial function, increased urinary catecholamines, blood pressure, and heart rate. Thus the proposed study model appears to be suitable to evaluate physiological and therapeutic effects in OSA. Clinical trial registered with www.controlled-trials.com (ISRCTN 93153804). Copyright ©2011 by the American Thoracic Society.